KARAKTERISTIK DAN MOTIVASI WISATAWAN MANCANEGARA YANG BERKUNJUNG KE PANTAI LAKEY, DOMPU, NUSA TENGGARA BARAT - Fitrullah, Muhammad; Oka Karini, Ni Made; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 2 (2019): Jurnal IPTA (December 2019), 2019)
Lakey Beach has potential that is not shared by many other tourist attractions such as left-hand wave sweeping. Not only that, the life of the local people around Lakey Beach tourist attraction which is quite unique and still preserves customs is a special attraction for tourists who visit. For this reason, we want to know the Characteristics, Motivation of foreign tourists visiting Lakey Beach.The sampling technique uses the slovin formula and purposive sampling by distributing 100 open questionnaires to foreign tourists visiting Lakey Beach tourist attractions. The data analysis technique used in this research is descriptive qualitative is a technique that describes and interprets the meaning of the data that has been collected. Based on the results of research characteristics of foreign tourists visiting Lakey Beach based on age 15-30 years old 57 people (57%), the area of origin of Australia 41 people (41%), male gender 5 people (56%), the status of recreational trips / holidays 98 people (98%), sources of friends / family information 54 people (54%), frequency of visiting 63 people (63%), home stay accommodations 59 people (59%). While the intrinsic motivation of foreign tourists on the indicator want to have fun score of 4.2 (agree), want to channel the hobby of surfing / surfing the score of 4.09 (agree) has the highest liker score, while the lowest liker score on the indicator wants to visit friends / liker's family score 2.15 (disagree). Whereas the extrinsic motivation of foreign tourists on the highest liker score indicator is the leisure time score of 4.27 liker (strongly agree), while the indicator with the lowest liker score is conducting a comparative study of liker score 2.16 (disagree).